2015
DOI: 10.1038/ijosup.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and childhood obesity: a 12-country study

Abstract: OBJECTIVES: Few studies have investigated the association between the full range of birth weight and the risk of childhood obesity in high-, middle-and low-income countries. The aim of the present study is to assess the association between different levels of birth weight and the risk of obesity among children aged 9-11 years in 12 countries. METHODS: A multinational, cross-sectional study of 5141 children aged 9-11 years was conducted in 12 countries. Height and weight were obtained using standardized methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
76
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 33 publications
15
76
2
7
Order By: Relevance
“…In the context of the early programming hypothesis, some (pre-)pregnancy and perinatal factors have been repeatedly shown to correlate with offspring obesity. Macrosomia and large birth weight [6,7] as well as small size for gestational age [6,8,9] are associated with increased childhood adiposity and later onset of metabolic diseases. Among the maternal factors, the most noticeable characteristics are an elevated pBMI [10] , gestational diabetes mellitus (GDM) [3,11,12] , and preeclampsia [13] .…”
Section: Pregnancymentioning
confidence: 99%
“…In the context of the early programming hypothesis, some (pre-)pregnancy and perinatal factors have been repeatedly shown to correlate with offspring obesity. Macrosomia and large birth weight [6,7] as well as small size for gestational age [6,8,9] are associated with increased childhood adiposity and later onset of metabolic diseases. Among the maternal factors, the most noticeable characteristics are an elevated pBMI [10] , gestational diabetes mellitus (GDM) [3,11,12] , and preeclampsia [13] .…”
Section: Pregnancymentioning
confidence: 99%
“…Una tendencia similar se mostró en el International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE), que incluye 12 países de ingresos altos, medios y bajos (PN 3.500-3.999 g, OR 1,45; IC 95%: 1,10-1,92; > 4.000 g, OR 2,08, IC 95%: 1,47-2,93, comparado con el grupo de referencia: 2.500-2.999 g) (36). El estudio internacional también mostró una asociación positiva entre el peso al nacer y el puntaje Z de IMC (36).…”
Section: Discussionunclassified
“…El estudio internacional también mostró una asociación positiva entre el peso al nacer y el puntaje Z de IMC (36). Nuestros resultados concuerdan con los resultados de los estudios descritos, aunque el incremento de riesgo de exceso de peso en nuestra muestra es más evidente en niños que tuvieron peso al nacer > 4.000 g a 4.500 g (OR 2,03, IC 95%: 1,14-3,60).…”
Section: Discussionunclassified
“…Another multinational, cross-sectional study of 5141 children aged 9-11 years was conducted in 12 countries by Qiao et al, showed that the multivariable-adjusted odds ratios (ORs) of childhood obesity were significantly higher among children whose birth weights were 3500-3999 g (OR 1.45; 95% confidence interval (CI): 1.10-1.92), and 4400 g (OR 2.08; 95% CI: 1.47-2.93), compared with the reference group (2500-2999 g). 14 The positive association between birth weight and the odds of childhood obesity was seen in girls, whereas a U-shaped association appeared in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Oldroyd et al, Li et al and Qiao et al were in concordance with our study findings. [13][14][15] Another study conducted by Hirschler et al concluded that low birth weight is not associated with overweight/obesity in children, but high birth weight was associated with overweight/ obesity and metabolic syndrome. …”
Section: Discussionmentioning
confidence: 99%